Potensi Ekstrak Etanol dan Fraksi-Fraksinya Dari Tiga Varietas Jahe Sebagai Agen Antibakteri Terhadap Staphylococcus aureus - Dewi Dianasari; Endah Puspitasari; Indah Yulia Ningsih; Bawon Triatmoko; Fauzia Ken Nasititi (Universitas Muhammadiyah Surakarta, 2020)
One of the natural ingredients that to be used to inhibit bacterial growth is the Zingiber officinale. In Indonesia, there are 3 types of ginger which are distinguished by morphology, namely ‘emprit ginger (Zingiber officinale var. Amarum), ‘ gajah’ ginger (Zingiber officinale var. Officinarum), and red ginger (Zingiber officinale var. Rubrum). This research was conducted to determine the activity of extracts and fractions of three ginger varieties in inhibiting the growth of Staphylococcus aureus using the disc diffusion method. The test group consisted of ethanol extract, n-hexane fraction, and ethyl acetate fraction from 3 ginger varieties, concentrations of 5, 10, 20% w / v, gentamicin 10 μg (positive control) and 10% DMSO (negative control). The test results showed that ethanol extracts and fractions from the rhizomes of three varieties of ginger have the ability to inhibit S. aureus at concentrations of 5, 10, and 20% w / v, increasing the concentration will increase the diameter of the inhibition zone. At a concentration of 20% of all samples, the one with the greatest resistance was the n-hexane fraction (diameter of inhibitory zone of emprit ginger 9.80 mm, elephant ginger 9.78 mm, and red ginger 9.90 mm). The difference in ginger variety only affects the antibacterial activity of the ethanol extract, but not the n-hexane and ethyl acetate fractions.